Advancement in Gene therapy: Current and Future of Gene Therapy - Shafee Ur Rehman (Kashmir Journal of Science)
Genetic diseases are serious health issues worldwide, caused by changes in gene structure due to mutations in single or multiple genes. Currently, no definitive treatments or medicines are available to cure these disorders. Gene therapy, a medical approach that utilizes genetic material, offers potential for preventing and treating diseases by addressing their underlying causes rather than relying on traditional methods like medication and surgery. This technique has shown promise in certain conditions by altering genetic material, enabling the body to produce desirable proteins or medications. However, gene therapy remains unavailable for most diseases and is still largely in the experimental stage for many conditions. This review investigates the current and future status of gene therapy not only for genetic disorders but also for life-threatening diseases such as cancer, cardiovascular disease (CVD), and diabetes. Additionally, the applications and limitations of gene therapy were evaluated. A review of recent research concluded that while rare or inherited genetic disorders could potentially be prevented or cured by precisely targeting their root causes, significant challenges remain. Rather than solely managing blood disorders, retinal diseases, and neuromuscular conditions, gene therapy can potentially eliminate these conditions. Furthermore, gene-based therapies offer expansive possibilities beyond rare genetic disorders, paving the way for broader therapeutic applications in the future.